A Comparison Between Save The Last Word For Me And Listen-Read-Discuss (Lrd) Strategies On Students’ Reading Comprehension At Smpn 1 Teluk Pinang - Martina Napratilora (Indonesian Journal of Learning Education and Counseling, 2018)
Abstract: The aim of the study wasto find out whether there is any significant difference between students’ reading comprehension using Save the Last Word for Me strategy and students’ reading comprehension using Listen-Read-Discuss (LRD) strategy through assessment of their reading comprehension. The study utilized Quasi Experimental Design Non-equivalent Pre-test and Post-test Group Design. The participants of the study comprised 76, year two students of Junior High School 1 Teluk Pinang. Save the Last Word for Me and Listen-Read-Discuss (LRD) strategies were used on two experimental groups which experimental group 1 (n= 38) using Save the Last Word for Me strategy and experimental group 2 (n= 38) using Listen-Read-Discuss (LRD) strategy. Data were collected using pre-test and posttest of students’ reading comprehension test. Quantitative data were analyzed using descriptive and inferential statistics. The finding showed significant difference in reading comprehension score between the experimental group 1 and experimental group 2 through Save the Last Word for Me and Listen-Read-Discuss (LRD) strategies. Key Words: Save the Last Word for Me strategy, Listen-Read-Discuss (LRD) strategy, Students’ Reading Comprehension, Abstrak: Tujuan dari penulisan ini adalah untuk mengetahui pemahaman membaca siswa menggunakan strategi Save the Last Word for Me dan Listen-Read-Discuss (LRD). Jenis penelitian ini adalah penelitian Kuasi-eksperiment atau perbandingan eksperimen dengan menggunakan pre-test-posttest design. Penelitian ini melibatkan 76 peserta yang terdiri dari kelompok eksperimen 1 dan kelompok eksperimen 2 dari siswa SMPN 1 Teluk Pinang. StrategiSave the Last Word for MedanListen-Read-Discuss (LRD)digunakanpadaduakelasexperimen yang manakelasexperimen 1 dengan sample 38 siswamenggunakan strategy Save the Last Word for Me dankelasexperimen 2 dengan sample 38 siswamenggunakanstrategiListen_Read-Discuss (LRD). Pengumpulan data melalui test pemahamankemampuanmembacasiswamelalui pre-test dan post-test. Data kuantitativedianalisamenggunakan descriptive dan inferential statistic.Hasil penelitian menunjukan bahwa adanya pengaruh yang signifikan dari nilaipemahamanmembacasiswaantarakelasexperimen 1 dan experiment 2 melaluistrategi Save the Last Word for Me and Listen-Read-Discuss (LRD). Kata kunci: starategi Save the Last Word for Me, strategi Listen-Read-Discuss (LRD) dan pemahaman membaca siswa.